Signs of the Baroque the art space and stylistic plane of William Shakespeare's “the Tempest” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article presents an attempt to explore the influence of Baroque aesthetics in the drama of Shakespeare. In the play “the Tempest” is applied to the Baroque instrumentation at the level of plot, drama and emotion of the concept of heroes. Using the techniques of the Baroque is seen as a means of free reflection of the dynamism of life, of contradictions and antinomies of the era. Shakespeare was acutely perceived the contradictions of his time. Hence the dynamics and drama of his works, the richness of struggle, clashes, conflicts. A deep comprehension of the trends of the time and led to the dynamic attitude of Shakespeare to the present, along with the growth of the skill determines the evolution of his work. Baroque is born in the depths of the late Renaissance and reflects the world in all its complexity, the multiplicity of the manifestations of infinity and change. Play “the Tempest” combines different means of creating and transforming reality, it combines illusion and reality, beauty and horror, the thirst for a happy life and tragedy. Art space and style pieces recreate the inconsistency of the world, which in the view of the author is a solid maze, where the individual is faced with different powers and is constantly being tested for spiritual vitality.
Keywords: illusiveness; spectacle; baroque performance; “to be – to seem”; “play within a play”; “mirror effect”